2014
DOI: 10.5539/ies.v7n2p25
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Information and Communication Technology Integration in Teaching and Learning in Institutions of Higher Learning

Abstract: Employing survey research design of the ex-post facto type, this study examined information and community technologies integration in teaching and learning in institutions of higher learning in Delta State, Nigeria. Four research questions and four hypotheses guided the investigation. Descriptive statistical tools such as mean and standard deviation were used to answer the research questions while t-test of significant difference was used to test the hypotheses. A sample of 560 students and lecturers were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
7
0
3
Order By: Relevance
“…These findings align with the findings of other studies. Asiyai (2014) found that a lack of governmental and institutional support would negatively influence faculty members' use of ICT in their educational practice. Salehi et al (2014) found that the availability of adequate budgets and suitable technical and structural resources would encourage faculty members to use ICT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings align with the findings of other studies. Asiyai (2014) found that a lack of governmental and institutional support would negatively influence faculty members' use of ICT in their educational practice. Salehi et al (2014) found that the availability of adequate budgets and suitable technical and structural resources would encourage faculty members to use ICT.…”
Section: Resultsmentioning
confidence: 99%
“…These findings align with the findings of other studies. For instance, Asiyai, (2014) found that faculty members and students believed that the integration of ICT in their educational practice had several benefits including: enhancing the quality of their teaching, matching learning styles, and enhancing collaborative networking and research. Salehi, et al (2014) reported that "educational benefits" was one of four factors that encouraged faculty members to integrate ICT into their educational practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asimismo, y en el contexto del Espacio Europeo de Educación Superior, la utilización de recursos digitales como redes sociales permite y favorece todo aquel aprendizaje que se asocia al nuevo paradigma que habla del trabajo en equipo, feedback, aprendizaje autónomo…, facilitando metodologías más activas y participativas (Cabero, Ballesteros, y López, 2015;Gómez, Roses, y Farias, 2012;Marquès y otros, 2006) y expandiendo el acceso a la información en cualquier lugar y momento (Ifeoma, 2014).…”
Section: Introductionunclassified
“…In a report released in 2012, the OCED proposed that ICT literacy is a multidimensional construct consisting of three separate components: the technical use of software and hardware, engagement in cognitive processes, and the extent of literacy tasks via reading and writing of digital materials (Asiyai, 2014). However, most existing research utilises cognitive and technical components combined as if they are homogenous proxies for overall ICT literacy suggesting it is one-dimensional in nature (Oliver & Goerke, 2008;Slechtova, 2015).…”
Section: The Need For Integrated Ict Literacy Measurementsmentioning
confidence: 99%